Modeling the impact of temperature on the release of Aedes aegypti infected with Wolbachia for DENV biocontrol (2025)
Aedes aegypti is the primary vector of dengue virus (DENV). Various control methods have been developed; however, their efficiency is limited. The release of A. aegypti transinfected with the bacterium Wolbachia is an innovative approach to control the transmission of this disease. However, increasing temperatures affect its efficiency and effectiveness. A mathematical model was developed incorporating parameters for reproduction, mortality, cytoplasmic incompatibility and loss of Wolbachia infection. Different scenarios were simulated, varying in release frequency, magnitude of the intervention and temperature. Results demonstrated that higher temperatures (32 °C) delay the establishment of this bacterium within the vector population and reduces its capacity to control DENV transmission. These findings underline the critical role of temperature in designing effective mosquitoes release programs and contribute to optimizing strategies for DENV control under diverse conditions.